Violation of consumer law in the financial system administrative indemnity processes before INDECOPI - Callalla Mamani, Jaime Arturo (2020)
We sought to compare the satisfaction of patients on hemodialysis, in the objective of the investigation is to determine whether the consumer of financial products and / or services from 2012 to 2015 has the possibility of obtaining relief, restitution and administrative compensation. This is a documentary study carried out on 367 users of the Ilo finance companies, based on the instrument "Observation form to measure the compensation of the finance companies for defective products and services" authored by the researcher. The financial companies, through INDECOPI, in 55.9% of the cases, offer remedial reparation to the users who complain and complain in the instances of the same, in 3.8% of the cases what is claimed is partially granted, and in 40.3% of cases, what was claimed or reported is not granted. The research hypothesis is approved, because defective products and services are repaired and restored. In INDECOPI's sanctioning procedures, there is restitution of what is claimed in full or in part, but no compensation is granted through administrative channels. Therefore, the investigation hypothesis is approved, because the sanctioning procedures are ineffective to offer administrative compensation to the users who complain or complain to the Ilo financial companies